Computational identification of plastic-degrading enzymes in ocean microbiomes - Sophie Li; Wencai Zhang (Scientific Reports)
Abstract With about 7 billion metric tons of plastic waste already in our environment and over 20 million metric tons of plastic produced annually, plastic waste has become a major global problem. Current methods to address this problem, such as incineration and landfills, are unsustainable and environmentally harmful. More trending approaches, such as plastic degradation using microbial enzymes, are rarely efficient enough to be applied industrially. To fill this gap in our knowledge, we developed a computational method called IPDE (Identification of Plastic Degrading Enzymes) to systematically identify promising enzymes, enzyme combinations, and microbial species for effective plastic waste degradation. Using IPDE, we discovered 50 and 86 enzymes in ocean and topsoil microbiomes, respectively, with at least 46% of these 136 enzymes highly likely to have a role in plastic degradation. Additionally, we identified 43 ocean enzyme combinations and 12 topsoil enzyme combinations, 20% of which contain enzymes that co-occur in the same metabolic pathways. Furthermore, we found 72 operational taxonomic units, with genus-level information available for 20 of them and 18 (25%) of them suggested in literature to be associated with plastic degradation. Our study identified promising plastic-degrading enzyme candidates for future experimental validation, functional studies, protein engineering, and industrial applications. The IPDE tool, which can be applied to other samples for further validation, is freely accessible at https://github.com/SophieL8/Plastic-degrading-enzymes .